Konsep Pendidikan Ibrani dalam Perjanjian Lama dan Implikasinya bagi Pelayanan Sekolah Minggu - yosia, yosia; Rembang, Gabriel Nuhk (STT INDONESIA MANADO, 2024)
Abstract: Sunday school education is often ignored and considered inferior to formal education. Even though the role of Sunday school is very important for the growth of Christian children’s faith, this article will examine the concept of Hebrew education from the Old Testament which then has an impact on today’s Sunday school services. The concept of Hebrew education is used as a model whose principles can be emulated so that Sunday school services can be carried out more optimally. Using descriptive qualitative methods through literature study, researchers found that Hebrew education is comprehensive, collaborative and theocentric. Therefore, several of these principles can be applied in Sunday school, namely first, Sunday school material must be comprehensive. Second, parental involvement is very important in children’s education at Sunday school. Third, the goal of education is to know God, carry out His commandments and live ethically. Abstrak: Pendidikan sekolah minggu seringkali diabaikan dan dianggap lebih rendah daripada pendidikan formal. Padahal peranan sekolah minggu sangat penting untuk pertumbuhan iman anak-anak Kristen. Artikel ini hendak mengkaji konsep pendidikan Ibrani dari Perjanjian Lama yang kemudian berdampak untuk pelayanan sekolah minggu masa kini. Konsep pendidikan Ibrani dipakai sebagai model yang dapat dicontoh prinsip-prinsipnya sehingga pelayanan sekolah minggu dapat dijalankan lebih maksimal. Dengan metode kualitatif deskriptif melalui studi pustaka, peneliti menemukan hasil penelitian bahwa pendidikan Ibrani bersifat komprehensif, kolaboratif dan teosentris. Karena itu, beberapa prinsip ini dapat diterapkan di sekolah minggu yakni pertama, materi sekolah minggu harus komprehensif. Kedua, keterlibatan orang tua sangat penting dalam pendidikan anak di sekolah minggu. Ketiga, tujuan pendidikan yakni mengenal Allah, menjalankan perintah-Nya dan hidup beretika.